2015
DOI: 10.1002/2014jc010397
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and propagation of Denmark Strait overflow water anomalies in the Irminger Basin

Abstract: Denmark Strait Overflow Water (DSOW) supplies the densest contribution to North Atlantic Deep Water and is monitored at several locations in the subpolar North Atlantic. Hydrographic (temperature and salinity) and velocity time series from three multiple-mooring arrays at the Denmark Strait sill, at 180 km downstream (south of Dohrn Bank) and at a further 320 km downstream on the east Greenland continental slope near Tasiilaq (formerly Angmagssalik), were analyzed to quantify the variability and track anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 41 publications
(72 reference statements)
7
51
0
Order By: Relevance
“…3c), which was added to DSOW to agree with the cascading events occurring along DSOW pathway (e.g. Pickart et al, 2005;Falina et al, 2012;Jochumsen et al, 2015). The net volume transport of the shallow core of PIW across OVIDE 2014 is in agreement with previous estimates of around −2 Sv entering from the Arctic Ocean (barely −2 Sv reported by Pickart et al, 2005, and an average transport of −2.4 ± 0.3 Sv reported by Falina et al, 2012Falina et al, , for 2002Falina et al, -2004.…”
Section: Water Mass Volume Transports For 2014supporting
confidence: 78%
See 2 more Smart Citations
“…3c), which was added to DSOW to agree with the cascading events occurring along DSOW pathway (e.g. Pickart et al, 2005;Falina et al, 2012;Jochumsen et al, 2015). The net volume transport of the shallow core of PIW across OVIDE 2014 is in agreement with previous estimates of around −2 Sv entering from the Arctic Ocean (barely −2 Sv reported by Pickart et al, 2005, and an average transport of −2.4 ± 0.3 Sv reported by Falina et al, 2012Falina et al, , for 2002Falina et al, -2004.…”
Section: Water Mass Volume Transports For 2014supporting
confidence: 78%
“…4f), supporting the existence of entrainment of East Greenland shelf waters into DSOW (e.g. Pickart et al, 2005;Falina et al, 2012;Jochumsen et al, 2015). PIW is also found on the continental shelves and slopes of Greenland and Canada, with the greatest contribution found on the Canadian shelf.…”
Section: Water Mass Distribution For 2014mentioning
confidence: 62%
See 1 more Smart Citation
“…Occasionally, the warm water peaks are even registered at the westernmost mooring DS22 (not shown). It is likely that the warm water originates in the vicinity of the sill, where bottom temperatures in the northward flow are within the observed range (e.g., see Figure 1 in Jochumsen et al, ). Further north of the sill, similarly high temperatures are not found below approximately 350 m (Jónsson & Valdimarsson, , ; Smith, ).…”
Section: Discussionmentioning
confidence: 81%
“…Using more than two decades' worth of hydrographic data from the region of the sill, Mastropole et al (2017) revealed that the Arctic-origin overflow water from the NIJ is found in the deepest part of the strait, whereas the Atlantic-origin overflow water resides above this and to the west, in the vicinity of the East Greenland shelf break (the constriction of the strait forces the shelf break and separated EGC branches to move closer to each other). Downstream of Denmark Strait these overflow waters entrain ambient water from the Irminger Basin, which significantly increases the transport and modifies the hydrographic properties of the dense water plume (e.g., Dickson et al 2008;Jochumsen et al 2015).…”
Section: Introductionmentioning
confidence: 99%